Fabrication and Properties of Lignin Based Carbon Nanofiber (Journal of Fiber Bioengineering and Informatics, 2013)
Lignin, the second most abundant biopolymer on earth, has the potential as a low cost and renewableprecursor for carbon fibers. By creating lignin carbon nanofibers for lightweight structural composites forautomobiles and functional applications as electromagnetic shields, the value of lignin will be enhanced.Under the Lignoworks Biomaterials and Chemicals Network program, we demonstrated the feasibilityof producing carbon nanofibers from softwood Kraft lignin by electrospinning and heat treatment.The morphological, mechanical, and electromagnetic properties of the lignin carbon nanofiber werecharacterized. Results showed 10 times increase in strength for the lignin random nanofiber mats aftercarbonization. Alignment of fibers further improved the mechanical strength. By doping the ligninpolymer with carbon nanotubes and functional nanoparticles such as magnetite, we demonstrated thefeasibility of translating the strength and electromagnetic function respectively to the lignin nanofiberassemblies. The encouraging results demonstrated the potential of lignin as an engineering material thusestablishing a pathway for adding values to the abundantly available lignin.
Keywords: Lignin; Carbon Nanofiber; Mechanical Properties; Multifunctional Nanofiber